DESAIN PI DENGAN FEEDFORWARD CONTROLLER PADA MOTOR TRAKSI GUNA PENGURANGAN PENGARUH DISTURBANSI - Aprilia Dwi Setyawati; Moch. Rusli; Rini Nur Hasanah (Jurnal Mahasiswa TEUB, 2023)
In this study, an analysis was carried out on the design of the PI controller and feedforward control to reduce the influence of interference due to load torque. Feedforward control works by detecting disturbance or called interference then the magnitude of interference will be compensated by the feedforward controller so that interference is reduced and does not interfere with the output value set by the set point. The determination of Kp and Ki controller parameters is carried out using the optimum symmetrical method and the value of the controller parameters Kp = 11.752 and Ki = 0.42 is obtained. Keywords: Three phase induction motor, PI controller, feedforward control, symmetrical optimum Daftar Pustaka[1] Leonhard W., Control of Electrical Drives, Springer-Verlag, Berlin Heiderberg. New York Tokyo. 1985.[2] Smith, Carlos A., and Armando B. Corripio. 1997. Principles and Practice of Automatic Process Control, 2nd Edition. New York:John Wiley & Sons, Inc,.[3] Enache, S., Campeanu, A., Vlad, I. and Enache, M.A., 2019, March. Particular Dynamic States of Railway Traction Asynchronous Motors. In 2019 11th International Symposium on Advanced Topics in Electrical Engineering (ATEE) (pp. 1-5). IEEE.[4] Wahab, H.A. and Sanusi, H., 2008. Simulink model of direct torque control of induction machine. American Journal of AppliedSciences, 5(8), pp.1083-1090.[5] Imantaka, Christoper. 2016. Perancangan PI Kontroler Pada Kontrol Kecepatan Motor DC Dengan Kombinasi Pole Placement Dan Symmetrical Optimum. Malang: Skripsi Teknik Elektro Universitas Brawijaya Malang.[6] Baskoro, F. and Nugroho, S.E., 2021. Sistem Pengendalian Kecepatan Motor Tiga Fasa Menggunakan Metode Direct TorqueControl (DTC). Jurnal Teknik Elektro, 10(1), pp.81-89.